Dispensing of food supplements in the treatment and prevention of urinary tract infections - Setoca, Beatriz (2021)
Urinary tract infections constitute an important public health issue due to recurrence and antibiotic resistance. Currently, antibiotics are the standard therapy but non-antibiotic approaches, such as food supplements, could be beneficial and reduce bacterial resistance. This work aimed at a better understanding of the perception of health professionals involved in dispensing and counselling, in the community pharmacy, regarding the utility of these products as preventive alternatives and therapeutic approaches.